Management of enterocutaneous fistulas in UMAE Hospital de Especialidades Dr. Antonio Fraga Mouret La Raza hospital of specialties - Rebollar, Rossy M. (International Surgery Journal, 2023)
Background: Describes the management of enterocutaneous fistulas in UMAE specialty hospital "Dr Antonio Fraga Mouret La Raza". Methods: Descriptive, observational, retrospective and cross-sectional study, records were reviewed describing the management of patients with enterocutaneous fistulas, period from 01/01/2017 to 12/31/2021, each qualitative variable described in frequency and percentages, data processed by SPSS, quantitative variables described with measures of central tendency and dispersion. Results: The 90 patients were included, 76.7% male and 23.3% female, median age 56 years. Anatomical location with greater frequency (42.2%) in ileum; 98.8% of the fistulas were surgical etiology, 100% operated by open procedure, 51.1% of the patients did not present comorbidities prior to the condition, 37.5% received definitive conservative management and 62.2% definitive surgical treatment, 36.7% presented definitive cure and 27.8% were recurrent, 35.6% presented chronicity. Conclusions: Male sex was most affected, 58.9% received initial conservative management and 41.1% surgical treatment, so 37.5% received definitive conservative management and 62.2% definitive surgical management, of which 36.7% were cured compared to the 35.6% who cornified; which reflects that there is no high significance between cure and chronicity of patients treated with definitive management, either conservative or surgical, it is undoubtedly concluded that the most prevalent intrahospital treatment is definitive surgical.